Efektivitas Audit Forensik dalam Mengungkap Fraud Berbasis Digital - Muthi'a Handayani (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2026)
This study aims to analyze the effectiveness of forensic audits in uncovering digital-based fraud. The current development of digital technology has provided opportunities for fraud perpetrators, particularly those involving information systems and electronic transactions. This study used the Systematic Literature Review (SLR) approach. This approach is guided by PRISMA, with the identification, screening, eligibility, and inclusion processes of 21 scientific journals obtained from Google Scholar and related databases for analysis. The results of the scientific journal analysis indicate that forensic audits play a significant role in identifying digital fraud patterns. Forensic audits have proven relevant and strategic in supporting and addressing the challenges of digital-based fraud. Keywords: Forensic Audit, Digital Fraud, Investigative Accounting, Digital Forensics.